2015
DOI: 10.1097/ico.0000000000000296
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ocular Surface Squamous Neoplasia With Topical Aloe vera Drops

Abstract: Ongoing research is warranted because A. vera may represent a new therapeutic class of medications for OSSN treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…The three most studied and used compounds are interferon-α2b (IFN-α2b),[23–28] 5-fluorouracil,[29–32] and mitomycin C (MMC). [33–40] (Table 2) Anti-vascular endothelial growth factor (anti-VEGF),[4145] retinoic acid,[46,47] and aloe vera[48] have also been used but their efficacy is not well-established yet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three most studied and used compounds are interferon-α2b (IFN-α2b),[23–28] 5-fluorouracil,[29–32] and mitomycin C (MMC). [33–40] (Table 2) Anti-vascular endothelial growth factor (anti-VEGF),[4145] retinoic acid,[46,47] and aloe vera[48] have also been used but their efficacy is not well-established yet.…”
Section: Resultsmentioning
confidence: 99%
“…The use of aloe vera in the form of eye drops has been reported in one case,[48] with resolution after 3 months of continuous use 3 times per day. However, the lesion was not biopsy-proven OSSN at diagnosis due to patient refusal.…”
Section: Resultsmentioning
confidence: 99%
“…Aloe plants demonstrate antiproliferative, immunostimulatory and antioxidant properties. Aloe consists of the molecules aloin and aloe emodin which mediate the anti-proliferative activity [111, 112]. Studies have shown that aloe emodin can induce apoptosis in vitro [112].…”
Section: Main Textmentioning
confidence: 99%
“…Aloe consists of the molecules aloin and aloe emodin which mediate the anti-proliferative activity [111, 112]. Studies have shown that aloe emodin can induce apoptosis in vitro [112]. Acemannan is a D-isomer mucopolysaccharide in Aloe vera with immunostimulatory effects, likely inducing an anti-neoplastic outcome [111, 112] .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation